Networks of metaphors in the Hebrew Bible - Verde, Danilo; Labahn, Antje (Bibliotheca Ephemeridum theologicarum Lovaniensium, 2020)
In continuity with the previous BETL volumes on biblical metaphors, namely Metaphor in the Hebrew Bible edited by Pierre Van Hecke (BETL 187; 2005), and Metaphors in the Psalms co-edited by Pierre Van Hecke and Antje Labahn (BETL 231; 2010), this third volume intends to contribute to and foster biblical research on metaphors by focusing on a phenomenon that has only received scant attention thus far, namely the relationship and interplay between different metaphors in the texts of the Hebrew Bible. Biblical metaphors very often come in chains, especially in poetry, in which individual metaphors may interact in a number of ways, e.g. they may modify, reverse, shift, and even contradict or reinforce the previous ones. Biblical metaphors often create families of metaphors that form a genuine repertoire of images to think and talk about a specific target domain from multiple viewpoints. The same source domain often inspires clusters of thoughts about a wide variety of realities. The same "root metaphor" may run throughout an entire book or a section of a book, emerging on the surface level of the text in many ways and interacting with other metaphors along the text continuum. 'Networks of Metaphors in the Hebrew Bible' investigates biblical metaphors not as "isolated events of discourse" but as constantly intertwining and shaping a network of multiple interactions between the figures. --Book cover.